2018
DOI: 10.1108/meq-02-2017-0021
|View full text |Cite
|
Sign up to set email alerts
|

Does financial development improve environmental quality in Turkey? An application of endogenous structural breaks based cointegration approach

Abstract: Purpose The purpose of this paper is to investigate the long-run effect of financial sector development, energy use and economic growth on carbon emissions for Turkey, in presence of possible regime shifts over a period of 1960-2013. Design/methodology/approach Along with the conventional unit root tests, Zivot-Andrews unit root test with structural break has been employed to check the stationarity of variables. The cointegrating relationship between variables is investigated by using the autoregressive dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 49 publications
3
38
0
5
Order By: Relevance
“…[24] revealed that financial development significantly enhances the environmental degradation in the One Belt and One Road region. [18,43] reported that financial development improves environmental quality in Turkey. Similarly, FDI coefficient results indicate a positive significant and dominant effect on CO 2 in the long run in Pakistan.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] revealed that financial development significantly enhances the environmental degradation in the One Belt and One Road region. [18,43] reported that financial development improves environmental quality in Turkey. Similarly, FDI coefficient results indicate a positive significant and dominant effect on CO 2 in the long run in Pakistan.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…They accomplished that energy use and economic growth increase CO 2 emissions, whereas trade openness and financial development compact it. As studied by the [18] examined the interplay between financial development, energy use and GDP on CO 2 emissions. Using time-series data for Turkey for the period 1976-1986, results of the analysis revealed that financial development develops environmental quality while energy use and economic growth reduce it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, in reference to Ozturk's (2010) and Shahbaz and Sinha's (2019) arguments on the inconclusive results on the Environmental Kuznets Curve (EKC) hypothesis, some researchers examined the nexus among CO 2 emission, economic growth, and energy consumption (Al Mamun et al 2014;Asif et al, 2015;Dar and Asif, 2018;Nguyen & Wongsurawat, 2017;Phuong & Tuyen, 2018), and virtually all of them established a significant positive influence of economic growth and energy consumption on CO 2 emission. Similarly, some recent studies such as Phong et al (2018) found a positive influence of GDP and energy consumption on CO 2 in the long run, whereas urbanization was found to negatively influence CO 2 in the short run.…”
Section: The Nexus Between Urbanization and Economic Growthmentioning
confidence: 99%
“…Henceforth, researchers have gained attention in the recent years in investigating the relationship between financial sector development and environmental degradation. Several studies indicate clear evidence of the development of financial sector causing increased emissions of carbon dioxide (Ali et al, 2018;Cetin, Ecevit, & Yucel, 2018a;Charfeddine & Khediri, 2015;Dar & Asif, 2017;Javid & Sharif, 2016;Paramati, Alam, & Apergis, 2018;Xing, Jiang, & Ma, 2017). The studies found explanations for a positive effect on CO2 emissions from the financial sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The consequences of climate change, global warming, and degradation of the environment are already visible in the escalation of extreme weather events, increased storm intensity, changing the patterns of rainfall, and increasing the sea level. Such alterations have an adequate effect on the proper functioning of ecosystems, forest sustainability, and human well-being (Boutabba, 2014;Dar & Asif, 2017).…”
Section: Introductionmentioning
confidence: 99%